Writing and publishing in architecture and design - Massey, Anne, 1956- (Abingdon, Oxon : Routledge, 2024)
"This book outlines the process of writing and publishing research in the field of architecture and design. The book sets out to help researchers find a voice and find the best fit for their work. Information about the different types of publication on offer is set out, as well as how to make that important initial approach. From pitching an idea for a review in a magazine, to producing a journal article right through to the monograph, Writing and Publishing in Architecture and Design maps out the different steps for the novice author. Your first steps in publishing can be daunting, and the book offers material which will inspire confidence, by demystifying the publication process. It also includes valuable nuts and bolts material such as planning and structure, time management, writing styles, editing, production of the final manuscript and picture research. How do you turn your PhD into a book? How do you turn conference proceedings into a publication? Commissioning editors and authors share their experiences through interview and offer recipes for success as well as what to avoid. Key titles from the past are included as case studies, and their pathway to publication explored. This is an invaluable book for anyone working in the fields of architecture and design, with an ambition to publish"--
Keywords: Architectural writing; ARCHITECTURE / General; ARCHITECTURE / Reference; ARCHITECTURE / Study & Teaching